Manufacturing method for PEEK film laminate

Through the design of low-crystalline PEEK film stacking and high-crystalline PEEK film as buffer film, combined with heat sink and laser irradiation, the problem of surface burning in multi-layer PEEK film welding is solved, and a high-precision PEEK film stacking with controllable thickness is achieved.

JP7625207B2Active Publication Date: 2025-02-03SHIN ETSU POLYMER CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021021762
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-15
Publication Date
2025-02-03
Estimated Expiration
2041-02-15

AI Technical Summary

Technical Problem

The prior art is difficult to control the surface temperature when welding multi-layer PEEK films, resulting in surface burnout and difficult to expand to a film stack of 800 μm or larger, limiting the number of layers of the film.

Method used

Low-crystalline PEEK film stacking is used, high-crystalline PEEK film is used as a non-welded buffer film, and inter-film welding is achieved through heat sink and laser irradiation. The heat dissipation effect of the heat sink is used to avoid surface burning, and the separation process is simplified by the design of the non-welded buffer film.

Benefits of technology

The stable welding of multi-layer PEEK film is achieved, keeping the film surface state unchanged, and the film stack with a thickness of more than 800 μm can be produced, and the thickness control accuracy is high, avoiding surface burning and deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625207000001
    Figure 0007625207000001
  • Figure 0007625207000002
    Figure 0007625207000002
  • Figure 0007625207000003
    Figure 0007625207000003
Patent Text Reader

Abstract

To provide a method for producing laminated PEEK films by irradiating a film bundle consisting of stacked PEEK films with a laser beam and fusing these films together.SOLUTION: A method for producing laminated PEEK films includes: a placing step for preparing a film bundle (2) consisting of stacked low-crystal PEEK films (1), putting a first non-fused buffer film (4) composed of a high-crystal PEEK film onto one of the outermost surfaces of the film bundle (2), and pressure-welding a heatsink (3) to the opposite face to the face of the first non-fused buffer film that is in contact with the film bundle and placing it there; a fusing step for applying a laser beam (LB) to the first non-fused buffer film and the film bundle through the heatsink and fusing the low-crystal PEEK films together to make a laminate consisting of the low-crystal PEEK films; and an acquisition step for releasing the first non-fused buffer film from the laminate to obtain it.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a PEEK film laminate using laser light irradiation. [Background technology]

[0002] Conventionally, a method has been disclosed in which two thermoplastic resin molded bodies are placed in contact with each other and irradiated with infrared laser light from one of the resin molded bodies to weld them together (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4279674 Summary of the Invention [Problem to be solved by the invention]

[0004] In the method of Patent Document 1, it is necessary to control the temperature Ti of the contact portion between the resin molded bodies and the surface temperature Ts of the resin molded body on the infrared ray irradiation side. When this method is applied to welding a film bundle made of multiple overlapping resin films, it is necessary to suppress the rise in the surface temperature of the film bundle on the infrared ray irradiation side so that the surface does not burn, so there is a problem that it is difficult to increase the number of resin films constituting the film bundle. In particular, it is difficult to weld a film bundle made of multiple overlapping PEEK films, which are excellent engineering plastics, to a thickness of 800 μm or more by irradiating it with laser light.

[0005] The present invention provides a method for producing a PEEK film laminate in which a film bundle in which a plurality of PEEK films are stacked is irradiated with laser light, and these films are welded to each other. [Means for solving the problem]

[0006] [1] A film bundle consisting of multiple low crystallinity PEEK films was prepared. A first non-welded buffer film made of a highly crystalline PEEK film is placed on one outermost surface of the film bundle; a placement step of pressing a heat sink against a surface of the first non-welded buffer film opposite to a surface in contact with the film stack; a welding step of irradiating the first non-welded buffer film and the film bundle through the heat sink with laser light to weld the plurality of low-crystalline PEEK films to each other, thereby obtaining a laminate composed of the plurality of low-crystalline PEEK films; an obtaining step of removing the first non-welded buffer film from the laminate; A method for producing a PEEK film laminate comprising the steps of: [2] In the positioning step, a second non-welded buffer film made of a highly crystalline PEEK film is further laminated on the other outermost surface of the film bundle, In the welding step, the laser light is irradiated through the heat sink onto the first non-weld buffer film, the film bundle, and the second non-weld buffer film to weld the low-crystalline PEEK films together to obtain the laminate made of the low-crystalline PEEK films, The method for producing a PEEK film laminate according to [1], wherein in the obtaining step, the first non-welded buffer film and the second non-welded buffer film are separated from the laminate to obtain the PEEK film laminate. [3] The method for manufacturing a PEEK film laminate described in [1], wherein in the welding process, the heat sink and the first non-welded buffer film, and the first non-welded buffer film and the film stack are not welded to each other. [4] The method for manufacturing a PEEK film laminate described in [2], wherein in the welding process, the heat sink and the first non-welded buffer film, the first non-welded buffer film and the film stack, and the second non-welded buffer film and the film stack are not welded to each other. [5] The first non-welded buffer film and the second non-welded buffer film are each a highly crystalline PEEK film having a plurality of uneven structures formed on one surface thereof, and in the arranging step, the film stack and the first non-welded buffer film and the second non-welded buffer film are arranged so that the uneven structure forming surfaces are in contact with the film stack, and The method for producing a PEEK film laminate according to [2] or [4], further comprising a transfer step in which the uneven structure of at least the second non-welded buffer film is inverted and transferred to the surface of the film stack during the welding step. [6] The method for producing a PEEK film laminate according to any one of [1] to [5], wherein the first non-welded buffer film is made of one or more highly crystalline PEEK films and has a total thickness of 30 to 300 μm. [7] The method for producing a PEEK film laminate according to [2], [4] or [5], wherein the first non-welded buffer film and the second non-welded buffer film are made of one or more highly crystalline PEEK films and each has a total thickness of 30 to 300 μm. [8] The method for producing a PEEK film laminate according to any one of [1] to [7], wherein the low-crystalline PEEK film has a moisture content of 1000 ppm to 4000 ppm with respect to the total mass of the low-crystalline PEEK film. Effect of the Invention

[0007] According to the method for producing a PEEK film laminate of the present invention, the PEEK films can be welded together while maintaining the surface condition without causing deformation or so-called ablation due to melting of the surface of the film bundle irradiated with laser light, and without changing the appearance of the PEEK film on the outermost surface of the film bundle. In addition, a PEEK film laminate can be obtained by welding a film bundle having a total thickness of more than 800 μm. Furthermore, since the thickness of the PEEK films constituting the film bundle hardly changes during welding, the thickness of the laminate can be easily controlled and the thickness variation is small. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram of a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a second embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic perspective view showing an example of a processing experimental device. [Figure 4] FIG. 1 is a conceptual diagram of a method for irradiating a film bundle with laser light. [Diagram 5] 1 is a photograph and a table showing an example of measuring the laser weld width. [Figure 6] 1A is a cross-sectional view of a film stack 2 produced by stacking PEEK films 1 in the thickness direction, FIG. 1B is a cross-sectional view of a heat sink 3 stacked on the top layer of the film stack 2, and FIG. 1C is a cross-sectional view of a non-welded buffer film 4 further stacked on the top layer of the film stack 2. [Figure 7] 1 is a photograph of a cross section of a film bundle 2 welded by laser light irradiation. [Figure 8] 1 is a table showing test conditions and test results for explaining Test Examples No. 1 to No. 10 of the first embodiment. [Figure 9] 1 is a table showing test conditions and test results for explaining Test Examples No. 11 to No. 20 of the first embodiment. [Figure 10] 1 is a table showing the conditions and results of tests that complement test groups 1 and 2 of the first embodiment. [Figure 11] 1 is a table showing test conditions for explaining Test Examples No. 21 to No. 24 of the second embodiment. [Figure 12] 13 is a table showing test results of Test Examples No. 21 to No. 24 of the second embodiment. [Figure 13] 1 is a table showing test conditions for explaining Test Examples No. 25 to No. 30 of the second embodiment. [Figure 14] 13 is a table showing test results of Test Examples No. 25 to No. 27 of the second embodiment. [Figure 15] 13 is a table showing test results of Test Examples No. 28 to No. 30 of the second embodiment. [Figure 16]1 is a table showing test conditions for explaining Test Examples No. 31 to No. 41 of the second embodiment. [Figure 17] 13 is a table showing some of the test results of Test Examples No. 31 to No. 41 of the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] First aspect A first aspect of the present invention is a method for producing a PEEK film, including a first positioning step, a second positioning step, a laser light irradiation step, and a welding and integration step. The first arrangement step is a step of preparing a film bundle in which a plurality of PEEK films are stacked, and fixing the heat sink to the surface of one of the outermost films of the film bundle by pressing the heat sink against the surface of the film bundle. The second arrangement step is a step of arranging a laser light irradiation means on the surface of the heat sink in a non-contact manner. The laser light application step is a step of applying laser light to the surface of the heat sink by the laser light application means, thereby applying laser light to the inside of the film bundle. The welding and integration step is a step in which the laser light irradiation means, the film bundle, and the heat sink are moved two-dimensionally relative to each other to weld the multiple PEEK films together and obtain a laminate. The heat sink used in this embodiment has a transmittance of 80% or more for incident light with a wavelength of 1 to 2 μm and a thermal conductivity of 40 W / m·K or more at 25° C., and the wavelength of the laser light irradiated to the film bundle is 1 to 2 μm.

[0010] <First placement process> 1, a plurality of PEEK films 1 are stacked to obtain a film bundle 2. A heat sink 3 is placed in pressure contact with the surface of the PEEK film 1 that constitutes one of the outermost surfaces of the film bundle 2.

[0011] The PEEK film 1 is a film formed of polyether ether ketone (PEEK). The PEEK film 1 may contain components other than PEEK, but it is preferable that the PEEK film 1 does not contain any substance that absorbs or reflects the laser light LB (for example, a filler such as a metal oxide). On the other hand, in order to improve the welding condition, it is preferable that the PEEK film 1 contains moisture. Although the factor that moisture affects the welding condition has not been clarified, it is speculated that when the film stack 2 is irradiated with the laser light LB, the heat of vaporization caused by the evaporation of moisture slows down the temperature rise to the melting point of the PEEK film 1, thereby suppressing the thermal decomposition of the PEEK film 1 caused by a sudden temperature rise.

[0012] The moisture content of the PEEK film is determined by the method described below, and the value is 1000 ppm to 4000 ppm, and for low-crystallinity PEEK film, it is 1000 ppm to 4000 ppm, preferably 2500 ppm to 4000 ppm. For high-crystallinity PEEK film, it is 1500 ppm to 3000 ppm, preferably 2000 ppm to 3000 ppm. If the moisture content is below 1000 ppm, the film is likely to decompose (burn) due to laser irradiation, and laser processing conditions that allow the film bundle to be welded and laminated while maintaining the state of the PEEK film cannot be obtained. On the other hand, the upper limit of the moisture content is a value corresponding to the saturated moisture content, and the value is different for low-crystallinity PEEK film and high-crystallinity PEEK film. If the moisture content is within the above range, the efficiency of welding PEEK films together can be further improved. The moisture content is a value measured by Karl Fischer coulometric titration method (Method B) defined in JIS K7251:2002 (ISO15512:1999). Examples of the measuring device include CA-100 (model name: manufactured by Nitto Seiko Air Analytec Co., Ltd.). The moisture content can be controlled by drying or water absorption treatment of the PEEK film. PEEK films with high moisture content are dried in a drying oven appropriately set at a temperature of 80°C to 120°C for a period of time until the desired moisture content is achieved. On the other hand, PEEK films with low moisture content can be adjusted to the desired moisture content by immersing them in water at room temperature or in warm water at 40°C to 80°C.

[0013] In this specification, a PEEK film with a crystallinity of 15% or less is called a low-crystallinity PEEK film, one with a crystallinity of 20% or more is called a high-crystallinity PEEK film, and one with a crystallinity of more than 15% but less than 20% is called an intermediate-crystallinity PEEK film. The crystallinity of the PEEK film is a value measured by the following method. The crystallinity of PEEK film can be measured by weighing out about 8 mg of a measurement sample from the PEEK film and using a differential scanning calorimeter (manufactured by SII Nanotechnologies, product name: EXSTAR7000 series X-DSC7000) at a heating rate of 10°C / min and a measurement temperature range of 20°C to 380°C. The heat quantity (J / g) of the crystal melting peak and the heat quantity (J / g) of the recrystallization peak obtained at this time are calculated using the following formula. Crystallinity (%) = (△Hm-△Hc) / 130×100 Here, ΔHc represents the heat quantity (J / g) of the recrystallization peak of the PEEK film when the temperature is increased at 10°C / min, and ΔHm represents the heat quantity (J / g) of the crystalline melting peak of the PEEK film when the temperature is increased at 10°C / min.

[0014] By using a low-crystalline PEEK film as the PEEK film, the efficiency of welding PEEK films together can be improved. The crystalline part of the PEEK film has a lower transmittance of laser light than the amorphous part, and it is thought that the energy of the absorbed laser light is insufficient for welding. It is presumed that when the crystallinity is within the specific range described above, the influence of the crystalline part is suppressed and welding by the amorphous part proceeds. In addition, since it is thought that water is absorbed by the amorphous part in the moisture content of the PEEK film, the low-crystalline PEEK film has the advantage that the moisture content is easy to adjust. The PEEK films 1 constituting the film bundle 2 may be either high-crystallinity PEEK films or low-crystallinity PEEK films, but it is more preferable that all of the PEEK films 1 constituting the film bundle 2 are low-crystallinity PEEK films.

[0015] The thickness of each PEEK film 1 can be, for example, 5 to 250 μm, preferably 10 to 200 μm, and more preferably 10 to 150 μm. The film bundle 2 can be produced by appropriately selecting the required number of PEEK films 1 in the above thickness range in combination considering the thickness of the welded laminate. In order to make the effect of the laser energy irradiated to the film bundle 2 acting on the interface of the overlapping PEEK films 1 constant, it is preferable to produce the film bundle 2 from PEEK films 1 of the same thickness, but this is not particularly limited. In addition, the PEEK film 1 is used that is formed by a known extrusion molding method. In this embodiment, as described later, the film bundle 2 is pressed against the heat sink 3 and irradiated with a laser to melt-laminated and integrated. The laminate after melt-laminated is laminated in a state where the thickness of the PEEK film 1 constituting the film bundle 2 is almost maintained by the pressing force of the heat sink 3 and thickness variations are eliminated, so that it has a great feature that it can be a laminate with excellent thickness accuracy. Generally, films produced by melt extrusion have a thickness variation of about ±5% of the set thickness, and the variation tends to increase as the film thickness increases. It is difficult to obtain films or sheets with the thickness accuracy obtained in this embodiment using the melt extrusion method.

[0016] The number of PEEK films 1 constituting the film stack 2 is determined by considering the thickness of the target laminate, and in terms of ease of handling the film and the efficiency of the film lamination process, a thicker film can be selected to reduce the number of laminated sheets, and one or two thinner films can be used to fine-tune the thickness. When considering ease of welding, it is sufficient to laminate many films of 50 μm or less, and there is no particular limit to the number of laminated sheets, which can be selected appropriately based on the laser processing conditions and the finished state of the laminate.

[0017] <Second placement process> Arranging the laser light irradiation means in a non-contact manner on the surface of the heat sink means that the surface of the heat sink and the laser light emission part are not in contact with each other, and there is an air layer or any gas layer between the surface of the heat sink and the laser light emission part.

[0018] <Laser light irradiation process> In FIG. 1, the laser light LB is irradiated so as to penetrate from the top to the bottom of the film bundle 2. The output of the laser light LB is adjusted appropriately according to the total thickness of the film bundle 2, the crystallinity and thickness of the PEEK film 1. This adjustment is performed based on the welding state in the surface direction and thickness direction of the film bundle 2. The laser light LB is scanned in the surface direction of the film bundle 2 by moving the laser light irradiation means and the film bundle 2 relative to each other in a two-dimensional manner. This scanning direction is expressed as the X direction and the Y direction, for example, as shown in FIG. 3. As shown in FIG. 3, the irradiation marks observed from the surface side of the film bundle 2 by the laser light LB are formed by setting the interval between the adjacent beam centers depending on the beam diameter and the operation speed. This interval and the laser output to be irradiated are set according to the thickness of the film bundle 2. If the laser output is low, the PEEK films 1 of the film bundle 2 may not be welded together, and conversely, if the laser output is too high, the temperature in the film bundle 2 may rise to the decomposition temperature of the PEEK film 1, which may cause problems such as the generation of air bubbles and decomposition products.

[0019] The device in FIG. 3 will be specifically described. Plates 12A and 12B are arranged on base 11 together with four support columns S1 to S4. Base 11 is preferably equipped with a vibration isolation function. XY stage 13 is arranged on plate 12A, and film stack 2 is fixed and arranged on a fixed table (not shown) on the XY stage. Plate 12B has an opening 16 for holding and fixing heat sink 3, where heat sink 3 is arranged. Support columns S1 to S4 are connected to plate 12A and 12B by a bearing structure, and plate 12A is structured to be movable in the vertical direction. Also, it is arranged so that laser beam LB (not shown) is irradiated in the direction of the arrow by laser beam irradiation means 14 from laser oscillator 15 via optical fiber 15'. Plate 12A is moved toward plate 12B to press film stack 2 arranged on XY stage 13 against heat sink 3. At this time, the base plates 12A and 12B are fixed by a fixing structure (not shown) so that the heat sink 3 and the film bundle 2 can be pressed against each other with an appropriate pressure. The appropriate pressure means that the heat sink 3 and the film bundle 2 are in close contact with each other over the entire area of ​​the contact surface, and the heat sink 3 is not deformed due to warping or curvature, and further means that when the PEEK film 1 constituting the film bundle 2 is melted by irradiation with the laser light LB, the pressure does not cause a large change in thickness from the original thickness or deformation of the film. In order to finely adjust the pressure, it is preferable to provide a buffer mechanism (not shown) for the vertical movement of the base plate 12A. Next, a predetermined moving speed and moving amount are set by the controller (not shown) of the XY stage, and the laser light LB is irradiated from a non-contact position onto the surface of the heat sink 3 while the film bundle 2 and the laser irradiation means 14 are moved two-dimensionally relative to each other, and the laser light LB that has passed through the heat sink 3 is irradiated into the inside of the film bundle 2. The laser light LB is irradiated over the entire thickness of the film bundle 2 while maintaining its beam diameter, and a welded portion corresponding to the beam diameter is formed.

[0020] 1, when welding the entire film bundle 2 from the top layer (the first PEEK film 1) to the bottom layer (the nth PEEK film 1) where the laser light is incident, the thickness of the film bundle 2 depends on the maximum laser energy that can be irradiated based on the maximum output of the laser oscillator, but is preferably 1500 μm or less from the limit of laser energy considering thermal damage to the heat sink 3 caused by heat when the laser light LB passes through the heat sink 3. In this embodiment, if the thickness of the PEEK film 1 superimposed near the top surface of the surface of the film bundle 2 that is pressed against the heat sink 3 is 50 μm or less, the heat dissipation effect of the heat sink 3 will have a greater effect than the radiant heat inside the film bundle 2 due to the laser irradiation, and the PEEK film 1 on the top surface in particular will peel off without being welded, so the thickness of the film bundle 2 must be set taking this into consideration. On the other hand, by increasing the thickness of the PEEK film 1 on the top surface of the film stack 2 that contacts the heat sink 3, the above-mentioned effects can be eliminated, and all of the PEEK films 1 on the film stack 2 can be welded and integrated without causing any effects on the film surface due to the heat sink effect. In this case, the thickness of the PEEK film 1 located on the top surface of the film stack 2 that is pressed against the heat sink 3 is preferably 100 μm or more and 200 μm or less. If the thickness of the PEEK film 1 to be overlaid on the bottom surface of the film stack 2 on the side opposite to the pressed surface of the heat sink 3 is also set to the same thickness, there is an effect of stabilizing the welded state on the bottom surface side.

[0021] The heat sink 3 used in this embodiment is a heat dissipation material having a transmittance of 80% or more for the laser light LB having a wavelength of 1 to 2 μm, and a thermal conductivity at 25° C. of 40 W / m·K or more. The shape of the heat sink 3 is not particularly limited, and examples thereof include a flat plate shape that is circular, sector-shaped, or rectangular when viewed from above. The thickness of the heat sink 3 is set in consideration of the transmittance and the material of the heat sink 3, and an example of this is a sapphire plate with a thickness of about 1 to 5 mm. The transmittance of sapphire is 80 to 90%, and its thermal conductivity at 25°C is 42 W / m K. In addition, its Young's modulus is 300 to 600 GPa, and its Poisson's ratio is 0.2 to 0.4. Examples of materials other than sapphire that can be applied to the heat sink 3 of this embodiment include a ZnSe (zinc selenide) plate (thermal conductivity 18 W / m·K at 25°C, Young's modulus 50-80 GPa, Poisson's ratio 0.2-0.3) with a thickness of about 1-4 mm, which is slightly inferior to sapphire in thermal conductivity, and a single crystal silicon plate (thermal conductivity 157 W / m·K at 25°C, Young's modulus 150-300 GPa, Poisson's ratio 0.2-0.3) with a thickness of about 1-5 mm. However, although silicon can generally be used for wavelengths of 2 μm or more, its transmittance is not as high as that of sapphire, being approximately 50% without a surface coating. In addition, silicon does not transmit wavelengths of 1-1.5 μm, and its use as a heat sink 3 is limited. The heat sink 3 is pressed against the film stack 2, and the pressing force is preferably in the range of 0.01 MPa to 0.10 MPa. More preferably, it is in the range of 0.02 to 0.08 MPa. If the pressing force is less than 0.01 MPa, the PEEK films 1 constituting the film stack 2 do not adhere closely, and gaps and unwelded portions are likely to occur. On the other hand, if the pressing force exceeds 0.10 MPa, the molten PEEK film 1 is excessively compressed and flows, causing the thickness of the PEEK film laminate to become thin and unstable, and may lead to bending or destruction of the heat sink 3. The heat sink 3 is preferably made of a material that does not bend much against this pressing force. For this reason, a sapphire plate with a large Young's modulus is preferable, and a sapphire plate with a Young's modulus of 450 GPa or more is particularly suitable.

[0022] In this embodiment, a laser beam having a wavelength of 1.0 to 1.5 μm or 2 μm is used. Among these, a laser beam having a wavelength of 2 μm is preferably used because it can obtain a favorable absorption state for the absorption wavelength of the PEEK film. An example of a laser beam having a wavelength of 2 μm is a thulium laser. A thulium fiber laser oscillator having a wavelength of 2 μm is preferably used as the laser oscillator, and continuous waves are preferable in order to uniformly weld the PEEK film laminate. The maximum output of the laser oscillator can be selected in the range of several tens to several hundreds of W depending on the film bundle, the crystallinity and thickness of the PEEK film, and the thickness of the laminate in the welding process described below. In addition, the fiber tip of the fiber laser oscillator has a fiber collimator structure, and the laser beam is emitted as a parallel beam by a collimating lens, and the beam diameter is preferably adjusted to φ1.0 mm to φ10.0 mm, more preferably φ3.0 mm to φ5.0 mm, taking into consideration the output of the laser beam, the efficiency of welding, the irradiation time required for welding, and the like. If the beam diameter is small, the processing efficiency decreases, and if the beam diameter is large, the laser output must be increased for thermal fusion, which may damage the heat sink or may reduce the uniformity of melting of the irradiated portion inside the film bundle due to the influence of the beam profile. Note that, in order to increase the processing efficiency, the laser light may be irradiated as multiple branched beams using a diffractive optical element or the like while maintaining the beam diameter.

[0023] <Welding and integration process> As illustrated in Figure 1, laser light LB having a wavelength of 1 to 2 μm is irradiated through a heat sink 3 toward the inside of the film bundle 2, and the irradiated areas of the film bundle 2 are welded together to obtain a PEEK film laminate in which multiple PEEK films 1 are welded together. After being irradiated with laser light LB, heat sink 3 is less likely to be welded to the surface of film bundle 2, and therefore can be easily separated from the surface of film bundle 2.

[0024] The method of irradiating the laser beam LB will be described in detail with reference to Fig. 4. The laser beam LB that has passed through the heat sink 3 is continuously irradiated in the planar direction inside the film stack 2 by two-dimensionally moving the laser beam application means 14 and the film stack 2 relative to each other in the laser beam scanning direction. Since the laser light LB is a continuous wave, the inside of the film bundle 2 is continuously laser processed and melted, forming the first laser processing line L1. At this time, the laser light irradiation interval P1 is appropriately adjusted taking into consideration the degree of beam overlap depending on the beam diameter and scanning speed of the laser light LB, the irradiation time at the laser light irradiation spot LB1, etc. Next, in order to form the processing line L2, the laser irradiation means 14 and the film bundle 2 are moved relatively at the line interval S2 at the laser irradiation line interval LS, and then the laser light LB is irradiated at an interval of P1 in the S3 direction. This is repeated until the processing of the desired area is completed. Note that although the laser light irradiation spots LB1 do not overlap in FIG. 4, the degree of overlap of the laser light irradiation spots LB1 and the degree of overlap of adjacent laser processing lines can be appropriately selected so that there are no unwelded parts, and taking into consideration the deterioration of the PEEK film due to excessive thermal processing by the laser light LB, the generation of bubbles due to thermal decomposition or melting, and the appearance of the film bundle 2 after welding.

[0025] A method for setting the laser irradiation line interval LS will be described with reference to FIG. 5. In order to weld the entire surface of the film stack, the laser irradiation line interval LS is set so that no gaps are created between the laser processing lines. FIG. 5 shows an example in which a line was irradiated onto the top surface of a film stack consisting of 20 layers of low crystallinity PEEK film with a thickness of 50 μm, and the width of the processed line was measured. The laser output was 50 W and the feed rate was 15 mm / sec. As shown in the figure, the laser processing line has a welding center (A) and welding peripheral parts (B) and (C), and the entirety of these (A), (B), and (C) becomes the welded part. The laser light used here has a Gaussian mode profile, and a difference occurs in the processing state between the center and peripheral parts of the laser irradiation. Taking this into consideration, the laser output and feed rate can be set so that welding is also performed in the welding peripheral parts. The table in FIG. 5 shows the measured values ​​of the laser welding widths of (A), (B), and (C) at measurement points No. 1 to 5, which were arbitrarily determined to be spaced apart at a predetermined interval, and their average values. From the measurement results shown in the figure, it can be seen that the gaps between the lines are eliminated if the laser irradiation line spacing LS is set to 1.56 mm or less. Note that the difference in the welding width of the welding periphery (B) and (C) is caused by a slight deviation in the angle of the laser light irradiation on the film bundle through the heat sink.

[0026] The method of arranging the film bundle 2 and the heat sink 3 will be described with reference to FIG. 6. The film bundle 2 is produced by overlapping the PEEK film 1 in the thickness direction. The PEEK film 1 may be a known one produced by, for example, a melt extrusion method, and is not particularly limited. The total thickness of the PEEK film laminate can be adjusted by the thickness and number of overlapping PEEK films 1. That is, the thickness of the PEEK film 1 is appropriately selected for the target total thickness, and the thickness and number of overlapping PEEK films 1 are determined so that the thickness is not thinner than the set layer thickness and is approximately equal to the total thickness, to produce the film bundle 2. At this time, PEEK films 1 of different thicknesses may be appropriately selected and used. In this embodiment, the PEEK film 1 on the surface in contact with the heat sink 3 may not be welded due to the heat sink effect, so it is necessary to set the number of overlapping films and thickness of the film bundle 2 taking this point into consideration. According to the manufacturing method of this embodiment, it is possible to weld and integrate the overlapped PEEK films 1 with almost no change in the thickness. Therefore, by simply selecting the thickness of the overlapping PEEK films 1, a laminate of any thickness that can be used as a sheet material or plate material can be obtained with small thickness variation, which is a great advantage in particular in comparison with sheet materials and plate materials produced by conventional extrusion molding. In addition, since the shrinkage of the PEEK film 1 due to the laser welding in this process can be almost ignored, there is an advantage that there are no restrictions on the direction (MD direction, TD direction) of the PEEK film 1 when overlapping, and the PEEK film 1 can be used efficiently. It is preferable to overlap pieces cut to the same size in order to align the overlapping positions of the PEEK films 1 when producing the film bundle 2. There is no particular need to apply heat or pressure when overlapping, but it is preferable to overlap the PEEK films 1 with as little air or wrinkles as possible between the films.

[0027] A method for evaluating the welding state of the film will be described with reference to FIG. 7. Photograph (1) is a photograph of the cross section of the film stack 2, in which the laser light LB irradiated and non-irradiated parts are adjacent, taken by enlarging it with a digital microscope. In the part not irradiated with the laser light LB, individual sheets of PEEK film that are not welded are observed overlapping each other. On the other hand, in the part irradiated with the laser light LB, the PEEK films are welded and integrated with each other. It can be seen that there is almost no difference in the total thickness between the non-irradiated part (non-welded part) and the irradiated part (welded part). Photograph (2) is a photograph of the cross section of the irradiated part taken by enlarging it. The internal welding state of the PEEK film laminate welded and integrated by the laser light LB irradiation can be evaluated by cutting the PEEK film laminate to be inspected with a blade or the like and observing the cross section. If the laser irradiation conditions are insufficient, parts of the PEEK film will peel off between the layers due to the pressure of the blade (parts indicated by arrows in the photograph). Photograph (3) is another photograph taken by enlarging the cross section of the irradiated area. The PEEK films are well welded together, and no peeling occurred when the cross section was cut out.

[0028] The laser light irradiation step and the welding / integrating step described above may be carried out simultaneously as a single step (laser light irradiation / welding / integrating step).

[0029] <Second aspect> A second aspect of the present invention is a method for producing a PEEK film laminate, the method including a positioning step, a welding step, and an obtaining step. The arrangement process is a process of preparing a film stack 2 consisting of multiple stacked low-crystalline PEEK films 1, stacking a non-welded buffer film 4 consisting of one or more highly crystalline PEEK films on at least one outermost surface of the film stack 2, and arranging the film stack 2 so that the non-welded buffer film 4 is pressed against a heat sink 3. The welding step is a step in which laser light LB is irradiated toward the inside of film bundle 2 through heat sink 3 and non-weld buffer film 4, and the irradiated portion of film bundle 2 is welded. The obtaining step is a step of obtaining a PEEK film laminate in which the plurality of low crystalline PEEK films 1 are welded to each other by separating the non-welded buffer film 4 that has not been welded to the film stack 2 from the film stack 2.

[0030] The second embodiment differs from the first embodiment in that the laser beam LB is applied while the non-welded buffer film 4 is sandwiched between the PEEK film 1 on the outermost surface of the film bundle 2 and the heat sink 3 (see FIG. 6(c)). Even after the PEEK films 1 of the film bundle 2 are welded together by irradiating the laser beam LB, the non-welded buffer film 4 is not welded to the heat sink 3 and the film bundle 2, so it can be easily peeled off from the film bundle 2. By disposing the non-welded buffer film 4, it becomes easy to maintain the surface of the outermost film after welding of the film bundle 2 in its original good condition. In addition, the non-welded buffer film 4 peeled off from the film bundle 2 after laser irradiation can be reused. This is based on the fact that the laser energy required for welding the high-crystallinity PEEK film is higher than that of the low-crystallinity PEEK film, as described in the test example described later, and utilizes the existence of processing conditions under which the high-crystallinity PEEK film and the low-crystallinity PEEK film are not welded even when they are overlapped and irradiated with a laser.

[0031] <Placement process> 2, a plurality of low crystallinity PEEK films 1 are stacked to obtain a film bundle 2, a first non-welded buffer film 4 is stacked on the upper surface of the film bundle 2, and a second non-welded buffer film 5 is stacked on the lower surface of the film bundle 2. Furthermore, the first non-welded buffer film 4 is arranged so as to be sandwiched between the film bundle 2 and a heat sink 3, and is arranged in pressure contact with the heat sink 3.

[0032] The explanation of the film bundle 2 and the low-crystalline PEEK film 1 that constitutes it is similar to the explanation of the low-crystalline PEEK film of the first embodiment, so duplicate explanations will be omitted.

[0033] The first and second non-welded buffer films 4, 5 are sheets made of one or more highly crystalline PEEK films. The number of sheets is not particularly specified, but from the viewpoint of workability, it is preferable that the number of sheets arranged is one. Highly crystalline PEEK film has the property of being difficult to weld with the laser energy that welds low-crystalline PEEK film. Although the details of this mechanism are unclear, it is speculated that this is due to the fact that highly crystalline PEEK film has more crystalline parts than low-crystalline PEEK film, as mentioned above.

[0034] The moisture content of the highly crystalline PEEK film used as the non-welded buffer films 4 and 5 is 1500 ppm to 3000 ppm, and preferably 2000 ppm to 3000 ppm. Within the above range, damage to the highly crystalline PEEK film caused by laser irradiation is reduced, the highly crystalline PEEK film is prevented from being welded to the film stack 2 by laser irradiation, and the highly crystalline PEEK film can be easily separated from the film stack 2 after laser irradiation. The moisture content is measured by the method described above.

[0035] The degree of crystallinity of the highly crystalline PEEK film is preferably 20% or more, more preferably 22% or more, and even more preferably 24% or more. When the thickness is within the above preferred range, the thermal fusion property can be reduced by the crystalline portion of the highly crystalline PEEK film.

[0036] The thickness of one or more highly crystalline PEEK films constituting the first and second non-welded buffer films 4, 5 can be independently set to, for example, 30 to 300 μm, and more preferably 50 to 200 μm.

[0037] If the thickness of the second non-welded buffer film 5 (total thickness in the lamination direction of the highly crystalline PEEK film) is sufficient, the laser light LB transmitted through the film stack 2 can be received. A part of the laser light LB incident on the second non-welded buffer film 5 may be absorbed inside the second non-welded buffer film 5, and the remaining part may be transmitted through the second non-welded buffer film 5. The laser light LB transmitted through the second non-welded buffer film 5 may be absorbed by another arbitrary member. In this case, even if another arbitrary member is heated and welded to the second non-welded buffer film 5, there is no problem because the second non-welded buffer film 5 is removed from the film stack 2 at a later stage. In addition, since it is difficult to weld the second non-welded buffer film 5 (highly crystalline PEEK film) to the bottom surface of the film stack 2 (lowly crystalline PEEK film), it is easy to remove the second non-welded buffer film 5 from the bottom surface of the target PEEK film laminate.

[0038] In order to obtain a laminate by the welding and integration process, it is necessary that the lowest layer of the film stack 2, i.e., the low crystallinity PEEK film 1 located at the bottom in the direction of laser light irradiation, is completely welded and integrated, and it is necessary to set processing conditions such as sufficient laser output to obtain this state. As a method for confirming this state, a method can be used in which an uneven shape is intentionally formed on the surface of the second non-welded buffer film 5 placed in contact with the low crystallinity PEEK film 1 located at the bottom layer, and this uneven shape is transferred to the surface of the low crystallinity PEEK film 1 located at the bottom layer by the pressure contact force of the heat sink 3 in the welding and integration process. For example, if multiple tiny dimples (concave portions) are formed in advance on the surface of the highly crystalline PEEK film constituting the upper surface of the second non-welded buffer film 5, and the surface of the low-crystalline PEEK film 1 arranged at the bottom layer of the film stack 2 is irradiated with laser light LB in contact with the surface of the low-crystalline PEEK film 1 arranged at the bottom layer of the film stack 2 as described above, multiple tiny transfer marks (convex portions) formed by inverting and transferring the dimples can be formed on the bottom surface of the film stack 2 (i.e., the PEEK film laminate), which can be visually confirmed with a low-magnification microscope. This state indicates that the low-crystalline PEEK film 1 arranged at the bottom layer has been sufficiently melted, and also indicates that the highly crystalline PEEK film, which is the second non-welded buffer film 5, has not been melted, i.e., has not been welded. This method makes it possible to confirm whether the above-mentioned laser output and processing conditions are appropriate and to set appropriate processing conditions. In actual production of a PEEK film laminate, the lamination and integration process may be performed by the above method, or the above method may be used to set the processing conditions to set appropriate processing conditions, and a step of using a second non-welded buffer film 5 having a smooth surface without dimples (depressions) in production may be used. This allows the production of a PEEK film laminate without transfer marks on the surface. It is also possible to form a similar uneven shape on the first non-adhesive buffer film 4 and transfer dimples (concave portions) onto the low crystalline PEEK film 1 located at the top layer of the film stack 2. Comparing the state of the transferred traces (convex portions) of the dimples (concave portions) on the low crystalline PEEK films 1 at the top and bottom layers of the film stack 2 can be used to adjust the laser processing conditions and set appropriate conditions. Furthermore, in the above step, in order to obtain a PEEK film laminate by welding all of the low crystalline PEEK films 1 constituting the film bundle 2, only the first non-welded buffer film 4 may be used. In other words, the second non-welded buffer film 5 may or may not be used.

[0039] The description of the heat sink used in this embodiment is the same as that of the heat sink in the first embodiment, so a duplicated description will be omitted. The explanation of the laser light and the laser device used in this embodiment is the same as the explanation of the laser light in the first embodiment, so a duplicated explanation will be omitted.

[0040] <Welding process> The explanation of the welding step in this embodiment is the same as the explanation of the laser light irradiation step and the welding and integration step in the first embodiment, so a duplicated explanation will be omitted.

[0041] <Acquisition process> After the welding process, the first non-welded buffer film 4 and the second non-welded buffer film 5 that were not welded to the film stack 2 are separated from the upper and lower surfaces of the film stack 2 to obtain a PEEK film laminate in which a plurality of low crystalline PEEK films 1 are welded to each other. As described above, the non-welded buffer films 4 and 5 are difficult to weld to the low crystalline PEEK film 1, so they can be removed simply by removing them.

[0042] The PEEK film laminate formed by the above process is made up of a plurality of low crystalline PEEK films 1 welded together. The upper surface of the PEEK film laminate is the surface onto which the laser light LB is incident, but as a result of heat dissipation by the heat sink 3 and the buffer effect of the first non-welded buffer film 4, no blackening or whitening due to scorching occurs, and the upper surface can exhibit a smooth surface similar to that of the original low-crystalline PEEK film 1. The lower surface of the PEEK film laminate is generally smooth like the upper surface, and the dimples of the first non-welded buffer film 4 and the second non-welded buffer film 5 that were in contact with the upper and lower surfaces may be transferred to the lower surface. Furthermore, if this transfer is not desirable for the PEEK film laminate, a PEEK film laminate with a smooth surface can be obtained by using non-welded buffer films 4 and 5 having smooth surfaces without dimples (concave portions) formed on the surface as in the above step, and welding and laminating the non-welded buffer films 4 and 5 having dimples under appropriate laser processing conditions obtained by using the non-welded buffer films 4 and 5 having dimples. EXAMPLES

[0043] [Test Group 1] First Aspect Tests No. 1 to No. 10 FIG. 8 shows the test contents and results. A film bundle was produced using only highly crystalline PEEK films, and a processing test was conducted under specified laser processing conditions. Specifically, laser processing was performed using the processing device shown in Figure 3 under the following conditions. 1) PEEK Film Highly crystalline PEEK film Thickness, crystallinity, and moisture content are shown in Figure 8. 2) Heat sink Material: Sapphire φ60mm circular shape Thickness: 4mm Laser light transmittance of 1.908μm wavelength: 85% Thermal conductivity at 25°C: 42 W m -1 ·K -1 Young's modulus 470GPa Poisson's ratio 0.3 Pressure contact force: 0.024MPa, 0.05MPa, 0.06MPa 3) Laser Oscillator Thulium fiber laser (IPG Model-50-1908) Wavelength: 1.908μm Maximum output: 50W Beam diameter: 4.3mm 4) Preparation of film bundle A film stack measuring 25 mm in length and 15 mm in width was prepared. No.1 to No.6 use only 50μm thick film No.7 25 sheets of 50 μm thick film were stacked, and one sheet of 150 μm thick film was stacked on top and bottom of them, with the 150 μm thick films on the side in contact with the heat sink and the bottom side. No.8 40 sheets of 20 μm thick film were stacked, and one sheet of 100 μm thick film was stacked on top and bottom of them, so that the 100 μm thick films were on the side in contact with the heat sink and the bottom side. No.9 25 sheets of 20 μm thick film were stacked, and one sheet of 100 μm thick film was stacked on top and bottom of them, with the 100 μm thick films on the side in contact with the heat sink and the bottom side. No. 10: 15 sheets of 50 μm thick film were stacked, and then one sheet each of 150 μm thick and 100 μm thick films were stacked so as to sandwich these, with the 150 μm thick film being placed on the side in contact with the heat sink. 5) Laser processing conditions See Figure 8 Welding dimensions: 20mm vertical, 10mm horizontal (10 lines of 20mm each)

[0044] For Tests No. 1 to No. 10, the PEEK film laminate was removed after laser processing and the welding state of the film stack was confirmed. As a result, there was unwelded PEEK film on the surface of the film stack that was in contact with the heat sink and on the lower surface side in the direction of laser irradiation, and each was easily peelable from the PEEK film laminate. By peeling these, a PEEK film laminate of the specified thickness was obtained, as shown in Figure 8. The obtained PEEK film laminate had good results, with the entire surface of the welding dimensions being welded, and there was no decomposition or blackening of the PEEK film due to heat, and no generation of air bubbles. That is, in this embodiment, a PEEK film laminate of the desired thickness can be obtained by setting the thickness and number of overlapping PEEK films constituting the film bundle, the number of layers to be peeled off unwelded after laser processing, and the corresponding laser processing conditions. The upper surface of the film bundle is left unwelded due to the heat dissipation effect of the heat sink, and the unwelded state of the lower surface side relative to the laser irradiation direction can be adjusted by the laser output and scanning speed. On the other hand, it is also possible to weld all of the PEEK films on the lower surface side of the film bundle by increasing the laser output using a higher output laser oscillator. In this case, it is necessary to provide a structure that absorbs the laser light that has passed through the film bundle and allows the PEEK film laminate to be peeled off. The appearance of FIG. 8 was evaluated according to the following criteria. The "condition evaluation of the PEEK film laminate" was rated as "good" if the entire surface of the welding dimensions was welded, and there was no decomposition or blackening of the PEEK film due to heat, or the generation of air bubbles.

[0045] [Test Group 2] First Aspect Tests No. 11 to No. 20 FIG. 9 shows the test contents and results. A film bundle was produced using only low crystallinity PEEK films, and a processing test was conducted under specified laser processing conditions. Laser processing was performed using the processing device shown in Figure 3 under the following conditions. 1) PEEK Film Low crystallinity PEEK film Thickness, crystallinity, and moisture content are shown in Figure 9. 2) Heat sink Material: Sapphire φ60mm circular shape Thickness: 4mm Laser light transmittance of 1.908μm wavelength: 85% Thermal conductivity at 25°C: 42 W m -1 ·K -1 Young's modulus 470GPa Poisson's ratio 0.3 Pressure contact force: 0.024MPa, 0.05MPa, 0.06MPa 3) Laser Oscillator Thulium fiber laser (IPG Model-50-1908) Wavelength: 1.908μm Maximum output: 50W Beam diameter: 4.3mm 4) Preparation of film bundle A film stack measuring 25 mm in length and 15 mm in width was prepared. No.11 to No.16: Only 50μm thick film is used No.17: 25 sheets of 50 μm thick film were stacked, and one sheet of 150 μm thick film was stacked on top and bottom of them, with the 150 μm thick films on the side in contact with the heat sink and on the bottom side. No.18: 40 sheets of 20 μm thick film were stacked, and one sheet of 100 μm thick film was stacked on top and bottom of them, with the 100 μm thick films on the side in contact with the heat sink and the bottom side. No.19: 25 sheets of 20 μm thick film were stacked, and one sheet of 100 μm thick film was stacked on top and bottom of them, with the 100 μm thick films on the side in contact with the heat sink and on the bottom side. No.20: 15 sheets of 50 μm thick film were stacked, and then one sheet each of 150 μm thick and 100 μm thick films were stacked so that they were sandwiched between them, with the 150 μm thick film coming into contact with the heat sink. 5) Laser processing conditions See Figure 9 Welding dimensions: 20mm vertical, 10mm horizontal (10 lines of 20mm each)

[0046] For Tests No. 11 to No. 20, the film bundles were removed after laser processing, and the welding state of the film bundles was confirmed. As a result, there was unwelded PEEK film on the surface of the film bundle that was in contact with the heat sink and on the lower surface in the direction of laser irradiation, and each could be easily peeled off from the PEEK film laminate, and by peeling these off, a PEEK film laminate of the specified thickness was obtained, as shown in Figure 9. The obtained PEEK film laminate had good results, with the entire surface of the welding dimensions being welded, and there was no decomposition or blackening of the PEEK film due to heat, and no generation of air bubbles. The appearance of FIG. 9 was evaluated according to the following criteria. The "condition evaluation of the PEEK film laminate" was rated as "good" if the entire surface of the welding dimensions was welded, and there was no decomposition or blackening of the PEEK film due to heat, or the generation of air bubbles.

[0047] From test groups 1 and 2, in this embodiment, a PEEK film laminate of the desired thickness can be obtained by setting the thickness and number of overlapping PEEK films 1 constituting the film bundle, the number of sheets to be peeled off without welding after laser processing, and the corresponding laser processing conditions. The upper surface of the film bundle is left unwelded due to the heat dissipation effect of the heat sink, and the unwelded state of the lower surface side relative to the laser irradiation direction can be adjusted by the laser output and scanning speed. On the other hand, it is also possible to weld all of the PEEK films on the lower surface side of the film bundle by increasing the laser output using a higher output laser oscillator. In this case, it is necessary to provide a structure that absorbs the laser light that has passed through the film bundle 2 and allows the laminate to be peeled off.

[0048] Furthermore, by laser processing a film stack in which the thickness of one PEEK film 1 on the surface pressed against the heat sink was 100μm and 150μm, a PEEK film laminate in which all the overlapping films were welded was obtained. By increasing the film thickness on the top surface of the film stack, a heat sink effect was achieved that maintained the state of the film on the top surface of the film stack, and the welded surface with the film directly below was in a state of sufficient energy. Since high crystallinity film requires more photon energy than low crystallinity film, the feed speed was set to 3mm / sec. and 5mm / sec, slower than that of low crystallinity film.

[0049] The results of test groups 1 and 2 showed that the number of highly crystalline PEEK films welded tended to be less than that of low-crystalline PEEK films. Therefore, as a complementary test, the difference in the number of welds of highly crystalline PEEK films and low-crystalline PEEK films was examined under the same laser welding conditions, and the results are shown in Figure 10. Note that in this test, the same highly crystalline PEEK films and low-crystalline PEEK films as those used for No. 5 in Figure 8 and No. 1 in Figure 9 were used.

[0050] According to the results in Figure 10, there is a difference in the number of sheets that can be welded under the same laser processing conditions, indicating that the laser processing conditions for welding low crystalline PEEK film are insufficient for welding high crystalline PEEK film. This suggests that there are processing conditions under which the films do not weld when high crystalline PEEK film and low crystalline PEEK film are overlapped.

[0051] [Test group 3] <Second embodiment> (Using non-welded buffer PEEK film) Test No.21~No.24 A film stack was made using only low crystallinity PEEK films, and a high crystallinity PEEK film was layered on at least one of the outermost surfaces as a non-welded buffer PEEK film, and this high crystallinity PEEK film surface was placed in contact with a heat sink, and the film stack was placed in a pressure-welded state. Then, as shown in Figure 11, laser processing was performed using the processing device configured in Figure 3 under the following conditions. 1) PEEK Film (1) Low crystallinity PEEK film in a film stack (Figure 11) (2) Highly crystalline PEEK film for non-welded buffer PEEK film (Figure 11) 2) Heat sink Material: Sapphire φ60mm circular shape Thickness: 4mm Laser light transmittance of 1.908μm wavelength: 85% Thermal conductivity at 25°C: 42 W m -1 ·K -1 Young's modulus 470GPa Poisson's ratio 0.3 Pressure: 0.064MPa 3) Laser Oscillator Thulium fiber laser (IPG Model-50-1908) Wavelength: 1.908μm Maximum output: 50W Beam diameter: 4.3mm 4) Preparation of film bundle Using the low crystallinity PEEK film of 1), a film bundle measuring 25 mm in length and 15 mm in width was produced with the number of layers shown in FIG. 5) Placement of non-welded buffer PEEK film 1) The highly crystalline PEEK film was placed on the top and bottom of the film stack, one on each side. 6) Laser processing conditions See Figure 11 Welding dimensions: 20mm vertical, 10mm horizontal (10 lines of 20mm each)

[0052] For Tests No. 21 to No. 24, the film bundle was removed after laser processing, and the welding state of the film bundle was confirmed. As a result, it was found that the surface of the film bundle that was in contact with the heat sink and the non-melting buffered PEEK film that was placed on the lower side in the direction of laser irradiation were not welded to the film bundle and could be easily separated from the film bundle. By peeling these off, a PEEK film laminate was obtained in which all of the low crystallinity PEEK films that make up the film bundle were welded. The test results are shown in Figure 12. The obtained PEEK film laminate had good results, with the entire surface of the welded dimensions being welded, and there was no decomposition or blackening of the PEEK film due to heat, and no generation of air bubbles. Furthermore, in the cross-sectional evaluation, no voids or air bubbles due to unwelded PEEK film were found on the cut surface.

[0053] The results in FIG. 12 were evaluated according to the following criteria. · Judgment on pass / fail of total film thickness after lamination; pass is within the target thickness of ±2.5%. The non-welded buffer PEEK film was rated as "good" if it could be peeled off without welding to the film stack and the surface condition of the PEEK film laminate was good. Appearance assessment; "Surface condition" must be ensured that the entire surface of the welding dimensions is welded, and that there is no decomposition or blackening of the PEEK film due to heat, and no air bubbles are generated. "Cross-section evaluation" is to ensure that there are no unwelded gaps between the layers of the PEEK film on the cut surface of the cross section. The "overall evaluation" was performed including the thickness variation of the laminate.

[0054] [Test group 4] <Second embodiment> (Use of non-welding protective PEEK film, dimple transfer) Test No.25~No.30 As a non-welded buffer PEEK film, a highly crystalline PEEK film was used, on one surface of which dimples (concave portions) with a diameter of 10 μm and a depth of 10 μm were arranged in a lattice pattern at intervals of 30 μm. A film stack was made using only low-crystalline PEEK films, and this highly crystalline PEEK film was superimposed on at least one of the outermost surfaces in a position where the dimple surface was in contact with the outermost surface side of the film stack, and this highly crystalline PEEK film surface was placed in contact with a heat sink, so that the film stack was pressed against it. Laser processing was then performed using the processing device configured as shown in Figure 3 under the following conditions as shown in Figure 13. 1) PEEK Film (1) Low crystallinity PEEK film in a film stack (Figure 13) (2) Highly crystalline PEEK film for non-welded buffer PEEK film (Figure 13) Dimples (recesses) with a diameter of 10 μm and a depth of 10 μm were formed on one surface of a 200 μm thick highly crystalline PEEK film, arranged in a lattice pattern at intervals of 30 μm. This formation can be achieved by a known method such as the transfer of a convex structure formed on a mold or roll surface during film formation. The non-welded cushioning PEEK film was placed so that the surface with the dimples (recesses) formed thereon was the surface that contacted the film stack. 2) Heat sink Material: Sapphire φ60mm circular shape Thickness: 4mm Laser light transmittance of 1.908μm wavelength: 85% Thermal conductivity at 25°C: 42 W m -1 ·K -1 Young's modulus 470GPa Poisson's ratio 0.3 Pressure contact force: 0.024MPa, 0.050MPa, 0.064MPa 3) Laser Oscillator Thulium fiber laser (IPG Model-50-1908) Wavelength: 1.908μm Maximum output: 50W Beam diameter: 4.3mm 4) Preparation of film bundle 1) Using the low crystallinity PEEK film, a film bundle measuring 25 mm in length and 15 mm in width was produced with the number of layers shown in Figure 13. 5) Placement of non-welded buffer PEEK film 1) The highly crystalline PEEK film was placed on the top and bottom of the film stack, or one film was placed on the top only, overlapping the film stack. 6) Laser processing conditions See Figure 13 Welding dimensions: 20mm vertical, 10mm horizontal (10 lines of 20mm each)

[0055] For Test Nos. 25 to 30, the film bundles were removed after laser processing, and the welding state was examined. The results are shown in FIG. 14 and FIG. As a result, the non-melting buffered PEEK film placed on the surface of the film bundle that was in contact with the heat sink and on the lower side in the direction of laser irradiation was not welded to the film bundle and could be easily separated from the film bundle, and by peeling them off, a PEEK film laminate was obtained in which all of the low crystallinity PEEK films that make up the film bundle were welded. The PEEK film laminate was welded over the entire surface of the weld dimensions, and there was no decomposition or blackening of the PEEK film due to heat, nor any generation of bubbles, resulting in good results. In addition, the surface of the PEEK film laminate was observed with a confocal laser microscope (model name: OLS4100, manufactured by Olympus Corporation). As a result, a convex structure was observed that was a transfer of the dimples (concave portions) of the highly crystalline PEEK film that had been overlaid on both sides of the PEEK film laminate, and it was confirmed that the film stack, which was made of low-crystalline PEEK film, had been sufficiently melted by the laser from the surface to the bottom surface.

[0056] Next, the thickness of the PEEK film laminate was measured. A Mitutoyo micrometer was used to measure the thickness at 20 points, and the thickness variation (range) was determined by evaluating the median, maximum, and minimum values. As a result, the thickness variation (range) including the transfer of the dimples was within 2.5%, resulting in a PEEK film laminate with little thickness variation and good thickness accuracy. The thickness of the PEEK film laminate varies slightly depending on the thickness accuracy of the low crystallinity PEEK film used, but this can be adjusted by using films of different thicknesses, the number of layers, the pressure contact force of the heat sink, etc.

[0057] [Test group 5] <Second embodiment> (Comparison of moisture content) Test No. 31 to No. 41 (No. 37 to No. 41 are comparative examples) A film stack was made using only low-crystallinity PEEK films with varying moisture contents, and a high-crystallinity PEEK film was superimposed on at least one of the outermost surfaces as a non-melting buffer PEEK film, and this high-crystallinity PEEK film surface was placed in contact with a heat sink, and the film stack was placed in a pressure-welded state. Then, as shown in Figure 16, laser processing was performed using the processing device with the configuration in Figure 3 under the following conditions. 1) PEEK Film (1) Low crystallinity PEEK film in film stack Moisture absorption: Immersed in 23°C water for up to 92 hours to absorb moisture Drying: Dry in a gear oven at 120℃ for 48 to 72 hours. (2) Non-melt buffered highly crystalline PEEK film Dimples (concave portions) with a diameter of 10 μm and a depth of 10 μm were formed on one surface of a highly crystalline PEEK film and arranged in a lattice pattern at intervals of 30 μm. 2) Heat sink Material: Sapphire φ60mm circular shape Thickness: 4mm Laser light transmittance of 1.908μm wavelength: 85% Thermal conductivity at 25°C: 42 W m -1 ·K -1 Young's modulus 470GPa Poisson's ratio 0.3 Pressure contact force: 0.05MPa 3) Laser Oscillator Thulium fiber laser (IPG Model-50-1908) Wavelength: 1.908μm Maximum output: 50W Beam diameter: 4.3mm 4) Preparation of film bundle Using the low crystallinity PEEK film and high crystallinity PEEK film of 1), a film bundle measuring 25 mm in length and 15 mm in width was produced with the number of layers shown in Figure 16. 5) Laser processing conditions See Figure 16 Welding dimensions: 20mm vertical, 10mm horizontal (10 lines of 20mm each)

[0058] For Nos. 31 to 36, which used low-crystallinity PEEK film with sufficient moisture content, the film stack was removed after laser processing and the condition of the PEEK film laminate was checked. No blackening due to laser irradiation occurred, and the condition of the PEEK film laminate was good. On the other hand, for Nos. 37 to 41, which used low-crystallinity PEEK film whose moisture content had been reduced by drying treatment, blackening occurred in the film stack due to thermal decomposition after laser irradiation. Figure 17 shows the external appearance photographs of some of the PEEK film laminates. [Explanation of symbols]

[0059] 1. PEEK film 2...film stack 3. Heat sink 4 ... First non-welded buffer film 5 ... Second non-welded buffer film LB...Laser light

Claims

1. A film bundle including a plurality of low-crystallinity PEEK films stacked on top of each other is prepared, A first non-welded buffer film made of a highly crystalline PEEK film is laminated on one outermost surface of the film bundle; a placement step of pressing a heat sink against a surface of the first non-welded buffer film opposite to a surface in contact with the film stack; a welding step of irradiating the first non-welded buffer film and the film bundle through the heat sink with a laser beam to weld the plurality of low-crystalline PEEK films to each other, thereby obtaining a laminate of the plurality of low-crystalline PEEK films; an obtaining step of removing the first non-welded buffer film from the laminate; A method for producing a PEEK film laminate comprising the steps of:

2. In the positioning step, a second non-welded buffer film made of a highly crystalline PEEK film is further superimposed on the outermost surface of the other of the film stacks, In the welding step, the laser light is irradiated through the heat sink onto the first non-welded buffer film, the film bundle, and the second non-welded buffer film to weld the low-crystalline PEEK films together to obtain the laminate made of the low-crystalline PEEK films; The method for producing a PEEK film laminate according to claim 1 , wherein in the obtaining step, the first non-welded buffer film and the second non-welded buffer film are obtained by separating them from the laminate.

3. The method for producing a PEEK film laminate according to claim 1 , wherein in the welding process, the heat sink and the first non-welded buffer film, and the first non-welded buffer film and the film stack are not welded to each other, respectively.

4. The method for manufacturing a PEEK film laminate according to claim 2, wherein in the welding process, the heat sink and the first non-welded buffer film, the first non-welded buffer film and the film stack, and the second non-welded buffer film and the film stack are not welded to each other.

5. The first non-welded buffer film and the second non-welded buffer film are each a highly crystalline PEEK film having a plurality of uneven structures formed on one surface thereof, and in the arranging step, the film stack and the first non-welded buffer film and the second non-welded buffer film are arranged so that the surfaces of the first non-welded buffer film and the second non-welded buffer film on which the plurality of uneven structures are formed are in contact with the film stack, and The method for producing a PEEK film laminate according to claim 2 or 4, further comprising a transfer step in which the uneven structure of at least the second non-welded buffer film is transferred in an inverted manner to the surface of the film stack in the welding step.

6. The method for producing a PEEK film laminate according to any one of claims 1 to 5, wherein the first non-welded buffer film is made of one or more highly crystalline PEEK films and has a total thickness of 30 to 300 μm.

7. The method for producing a PEEK film laminate according to claim 2, 4 or 5, wherein the first non-welded buffer film and the second non-welded buffer film are made of one or more highly crystalline PEEK films, and each has a total thickness of 30 to 300 μm.

8. The method for producing a PEEK film laminate according to any one of claims 1 to 7, wherein the moisture content of the low-crystallinity PEEK film is 1000 ppm to 4000 ppm with respect to the total mass of the low-crystallinity PEEK film.

Citation Information

Patent Citations

  • Printed wiring board and multilayer printed wiring board, and manufacturing methods of those

    JP2013157585A

  • Laminate and method for producing the same

    JP2019195945A

  • Percutaneous absorption type formulation

    JP2020033267A

  • Aromatic polyether ketone-layered product, and method for producing the same

    JP2020037237A

  • Laminated polyether ether ketone resin sheet, method of manufacturing the same

    JP2020163647A